IgG4 related lung disease mimicking multiple pleural disseminated lung cancer - Koya Ito; Yukiko Maeda; Akane Mita; Saori Aizawa; Arei Mizushima; Natsuko Taniguchi; Katsura Nagai; Hiroki Shomura; Atsuo Hattori; Toshiyuki Harada (Respirology Case Reports, 2022)
Key message IgG4‐related lung disease (IgG4‐RLD) can present with various types of radiological findings such as nodule, ground‐glass opacity, alveolar interstitial, and bronchovascular involvement. IgG4‐RLD generally manifests as mild clinical symptoms, despite evidence from the image findings. Herein we report an asymptomatic patient with IgG4‐RLD mimicking multiple pleural disseminated lung cancer.